2013
DOI: 10.1016/s1872-2067(12)60658-5
|View full text |Cite
|
Sign up to set email alerts
|

Aldol condensations of a variety of different aldehydes and ketones under ultrasonic irradiation using poly(N-vinylimidazole) as a new heterogeneous base catalyst under solvent-free conditions in a liquid-solid system

Abstract: An ultrasound-assisted aldol condensation reaction has been developed for a range of ketones with a variety of aromatic aldehydes using poly(N-vinylimidazole) as a solid base catalyst in a liquid-solid system. The catalyst can be recovered by simple filtration and reused at least 10 times without any significant reduction in its activity. The reaction is also amenable to the large scale, making the procedure potentially useful for industrial applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Developing cost-effective and eco-friendly processes and performing reactions with safe and greener reagents, solvents, and catalysts are crucial issues of organic synthesis research. In continuation of our recent studies [35][36][37], herein, the efficient catalytic activity of PVIm, as a functional polymer, for the synthesis of various bis(3-indolyl)methanes (BIMs) is described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing cost-effective and eco-friendly processes and performing reactions with safe and greener reagents, solvents, and catalysts are crucial issues of organic synthesis research. In continuation of our recent studies [35][36][37], herein, the efficient catalytic activity of PVIm, as a functional polymer, for the synthesis of various bis(3-indolyl)methanes (BIMs) is described.…”
Section: Resultsmentioning
confidence: 99%
“…PVIm, as a pH-sensitive functional polymer, can be protonated at acidic pH and de-protonated under basic conditions [32]. PVIm and its copolymers have been applied in the suppressing gene expression, as drug and protein delivery carriers [31], heavy metal removal via metal-binding chelating [33,34], catalysis [35][36][37][38], pervaporation [39], fuel cell [40], CO2 separation [41], and nanofiltration separation [42].…”
Section: Introductionmentioning
confidence: 99%
“…Developing more sustainable synthetic processes, improving the conventional industrial procedures, employing greener reagents and catalysts, and performing the reactions with high safety under low-risk conditions are crucial for organic synthesis research. With regard to our interest in the catalytic application of PVIm in organic synthesis, herein, the catalytic efficiency of PVIm as a biocompatible and biodegradable functional polymer is described for the synthesis of aliphatic, aromatic, and heteroaromatic nitriles from the corresponding aldehydes.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous applications in different academic and industrial fields have been reported for PVIm and its copolymers . For example, they have been applied as drug and protein delivery carriers in suppressing gene expression, efficient reagents against bacterial pathogens, chelating agents for the removal of many heavy metals, , catalysts, fuel cells, CO 2 separation, pervaporation, and nanofiltration separation …”
Section: Introductionmentioning
confidence: 99%
“…However, the use of an acid catalyst allows side reactions to be prevented, such as the Cannizzaro reaction, which occurs in strongly alkaline conditions [ 35 ]. Recently, greener conditions were developed using reusable catalysts such as Amberlyst-15 and Amberlite-200C, which are commercial acid-resins, or even solid base catalyst (e.g., poly( N -vinylimidazole)) coupled with ultrasonic irradiation under solvent-free conditions [ 36 , 37 ]. Although Claisen–Schmidt condensation is the most widely used method due to its simple procedure, other approaches have been described.…”
Section: Introductionmentioning
confidence: 99%